Activation of D2 dopamine receptor-expressing neurons in the nucleus accumbens increases motivation. - Cunha, Catarina Soares (2016)
Striatal dopamine receptor D1-expressing neurons have been classically associated with positive reinforcement and reward, whereas D2 neurons are associated with negative reinforcement and aversion. Here we demonstrate that the pattern of activation of D1 and D2 neurons in the nucleus accumbens (NAc) predicts motivational drive, and that optogenetic activation of either neuronal population enhances motivation in mice. Using a different approach in rats, we further show that activating NAc D2 neurons increases cue-induced motivational drive in control animals and in a model that presents anhedonia and motivational deficits; conversely, optogenetic inhibition of D2 neurons decreases motivation. Our results suggest that the classic view of D1-D2 functional antagonism does not hold true for all dimensions of reward-related behaviours, and that D2 neurons may play a more prominent pro-motivation role than originally anticipated.